Boîte à crayons, humour et célébrité au Québec : les caricatures d’Albert Chartier dans le journal Radiomonde (1940-1962) - Rannaud, Adrien (RACAR : Revue d'art canadienne / Canadian Art Review, 2025)
At the intersection of cultural history and the history of cartoon in Québec, this paper analyzes the staging and figurations of celebrity culture as they unfolded under the pencil of Albert Chartier in the periodical Radiomonde between 1940 and 1962. The author shows how cartoons represented the new show business during the 1940s and the 1950s, and how Chartier took advantage of a specific “grammar of humor” in his drawings. In a first part, the paper revisits Chartier’s journey through cultural press during the 1940s and 1950s. Then, it examines the stereotypes and figures that the artist uses to satirize celebrity culture in order to explore the underlying values circulating within the cartoons.